ANALYSIS OF WEED VEGETATION IN TEAK AND SENGON STANDS IN SUMBER GIRISUKO VILLAGE PANGGANG DISTRICT GUNUNGKIDUL REGENCY - Maryana, Maryana; Rizal AZ, Abdul; Aji Pangestu, Febriana (Journal TECHNO, 2024)
Weed vegetation refers to plants that grow in agricultural land, gardens, or other environments that are undesirable to humans. The aim of the research was to analyze weed composition and determine the value of weed diversity in teak plant stands and sengon plant stands. Analysis of weed vegetation on land with the SDR coefficient value of weed species, to see differences in weed composition between two stands using a community index. The research was carried out in Sumber Girisuko Village Panggang District, Gunungkidul Regency. Determining the research location used the purposive sampling method and weed sampling using systematic random sampling, while the analysis method used the quadratic method. The results obtained show that in this study 10 weed species were found from 6 families, namely Passifloraceae, Colchicaeae, Asteraceae, Poaceae, Convolvulaceae, and Verbenaceae. In the land under teak stands, 5 species were found with SDR values of 0.03-0.61, in land under sengon stands there were 8 species with SDR values of 0.02-0.48. The value of the community coefficient for the land under the teak and sengon stands was 16%, meaning that the weeds on the two lands were not uniform. The diversity index (H') value for land under teak stands is 1.10 and for sengon stands is 1.52, which means it is classified as moderate. The Simpson dominance index was found to be 0.40 in land under teak stands, and 0.27 in sengon stands, meaning that weed species were present but did not dominate.